ANALYSIS OF DETERMINANTS OF LABOUR ABSORPTION IN THE APEC-11 REGION (2010-2022) - Iqbal Manaf; Lestari Sukarniati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The labour aspect plays a vital role in national economic progress. This sector seeks to create adequate employment opportunities to absorb the new labour force. Aspects such as the quality, quantity, and accessibility of employment become crucial benchmarks of economic development. The main focus of this study is to see the relationship in the form of wages, industrial growth, FDI, inflation, and GDP to employment in the APEC-11 region. This research utilizes panel data, drawing on secondary information obtained from World Bank during the period 2010-2022. The research employs panel data analysis, specifically Fixed Effect Model which is analyzed using the Eviews10 application. The regression analysis outcome, indicate that only the industrial growth variable affects labor absorption while the wage, FDI, inflation, and GDP variables have no impacts on labor absorption. However, simultaneously all variables have a significant impact to labor absorption in the APEC-11 Region period 2010-2022.